The Utilization Of Feather Meal Fermented Using Bacillus sp. From Tiger Shrimp (Penaeus monodon) For Fish Feed of Silver Pompano (Tracchinotus blochii) Fingerling - Roma Uli Purba; Adelina '; Indra Suharman (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2017)
This research was conducted from May-July 2017. The purpose of this research was to know the best persentage using Feather meal fermented to subtitution fish meal in diets and the effect on growth and feed effeciency. This study uses a completely randomized design (RAL) with one faktor, 5 level treatments and 3 replications. Feeding trials was replacing with fish meal with Feather meal fermentation applied to P0 ( without feather meal fermented in diet), P1 (5% feather meal fermented in diet), P2( 10 % feather meal fermented in diet), P3 (15% feather meal fermented in diet), and P4 (20% feather meal fermented in diet). The result showed that the best treatment contained in P2 (10 % feather meal fermented in diet) with digestibility 23,21%, protein digestibility 56,56% , feed efficiency 72,66%, protein retention 11,88%, spesific growth rate 3,56% and survival rate 86,66%.